NON-COMMUNICABLE DISEASES: A CHALLENGE - Kumar, Sandip; Kaushik, Amit (Indian Journal of Community Health, 2012)
After completion of 65 years of independence, our country has witnessed remarkable progress in the health status of its population. However, over the past few decades, there has been major transitions in the country that have serious impact on health. Changes have been seen in economic development, nutritional status, fertility and mortality rates and consequently, the disease profile has changed considerabely. Though there have been substantial acievements in controlling communicable diseases, still they contribute significantly to disease burden of the country. Decline in morbidity and mortality from communicable diseases have been accompanied by a gradual shift to, and accelerated rise in the prevalence of, chronic non-communicable diseases (NCDs) such as cardiovascular disease (CVD), diabetes, chronic obstructive pulmonary disease (COPD), cancers, mental health disorders and injuries1. Researchers and policy makers around the world have been increasingly recognizing NCDs (Non communicable diseases) as a health and developmental emergency. NCDs are the leading cause of death in the South-East Asia Region, killing 7.9 million annually (55% of the total deaths in the Region). NCD deaths in region are expected to increase by 21% over the next decade.